Pemanfaatan Gofood Sebagai Strategi Komunikasi Pemasaran Dalam Penguatan Branding Salad Bulbul Kitchen - Evi Lia Fauziah; Jestiana Al Kayrani Rahmadhina; Yulia Dwi Lestari; Muhamad Fajar; Muhammad Fazrah; Ridwan Irawansyah (HUMANUS : Jurnal Sosiohumaniora Nusantara, 2025)
This study clearly shows that GoFood is not just a way to distribute food, but also a powerful marketing communication tool for culinary MSMEs. Especially in the case of Salad Bulbul Kitchen, the skill of using GoFood features such as seeing what customers say, giving awards to loyal customers, and processing data has succeeded in making their brand better known, making customers more actively interacting, and keeping customers. This data-based digital strategy has proven to be effective in strengthening brand position amidst the fierce competition for healthy food. This study suggests that other MSMEs should also start taking advantage of everything that digital platforms like GoFood can offer, not only to increase sales, but also as a means to build brands and analyze the market in a smart way. For further research, it would be good to compare various food delivery platforms to see how effective each platform is in helping MSMEs build their brands..